Renal Angiomyolipoma Mimicking a Well-Differentiated Retroperitoneal Liposarcoma - Honoka Fuse; Masaya Ito; Kosuke Takemura; Shuzo Ikuta; Toru Motoi; Tomotake Okuma; Madoka Kataoka; Fumitaka Koga (Case Reports in Urology)
A 37-year-old Burmese woman presented with an incidentally found retroperitoneal fat-containing tumor. The tumor was 9 cm in the longest diameter, surrounding the right kidney, and composed of homogenous adipose tissue with thickened septum-like structures and spotty nonadipose structures, which were enhanced on contrast-enhanced computed tomography and magnetic resonance imaging. The tumor did not show either a beak sign or synchronous angiomyolipoma-like lesion in the kidneys. The tumor had irregular septa, thin blood vessels, and spotty small soft-tissue nodules. The tumor did not contain any heterogeneously enhanced solid lesions suspicious for dedifferentiated liposarcomas. Based on these imaging findings, a clinical diagnosis of a well-differentiated liposarcoma was made. Under the consensus of a multidisciplinary cancer board, she was recommended to undergo core-needle biopsy to confirm the clinical diagnosis. However, she declined to undergo biopsy for financial reasons. She underwent kidney-sparing retroperitoneal tumor resection. Histopathologically, the tumor was an angiomyolipoma with positive immunostaining for HMB45 and Melan A. The present case suggests the importance of core-needle biopsy prior to surgical intervention for retroperitoneal fat-containing tumors.